2017
DOI: 10.1055/s-0043-111800
|View full text |Cite
|
Sign up to set email alerts
|

Rekanalisierung von Tränenwegsstenosen mittels Laserdakryoplastik unter Verwendung eines Diodenlasers – Vergleich der Erfolgsraten zum Erbium-YAG-Laser

Abstract: In a retrospective study, the success rates of laserdacryoplasty using a diode laser were defined and compared to success rates using an erbium : YAG laser. Using a diode laser at a wave length of 980 nm, thermal destruction of tissue leads to recanalization. Using an erbium : YAG laser at a wave length of 2940 nm, recanalization of punctual stenosis is achieved by formation of a cavitation bubble in a closed system. 94 patients (64 women, 30 men, mean age 60.8 years) with 107 absolute lacrimal duct stenoses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
(23 reference statements)
0
2
0
1
Order By: Relevance
“…But it is also found that a higher rate of postoperative complications such lacrimal bleeding and/or palpebral edema as compared to previous laser dacryoplasty [ 9 ]. Laser dacryoplasty for nasolacrimal recanalization has been in use for more than two decades [ 10 ]. The lasers employed include Nd-YAG, THC:YAG, Erbium:YAG, and the Diode laser [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But it is also found that a higher rate of postoperative complications such lacrimal bleeding and/or palpebral edema as compared to previous laser dacryoplasty [ 9 ]. Laser dacryoplasty for nasolacrimal recanalization has been in use for more than two decades [ 10 ]. The lasers employed include Nd-YAG, THC:YAG, Erbium:YAG, and the Diode laser [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Laser dacryoplasty for nasolacrimal recanalization has been in use for more than two decades [ 10 ]. The lasers employed include Nd-YAG, THC:YAG, Erbium:YAG, and the Diode laser [ 10 ]. The laser probes can be passed through the working channel into the NLD and then can be directly applied to the obstructed tissue with an end-on dacryoendoscopic visualization [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Langstreckige absolute Stenosen mit postsakkaler Lokalisation eignen sich weniger für eine DE. Insgesamt liegt der Langzeiterfolg bei etwa 60 %, kann aber durchaus bei relativer präsakkaler TNW-Stenose über 80 % betragen [25,29,30]. Nach einer endoskopischen Rekonstruktion werden die TNW vorübergehend durch Silikonverweilsonden gesichert (▶ Abb.…”
Section: Visuell Kontrollierte Transkanalikuläre Operationstechnikunclassified